Upaya Pelestarian Lingkungan Hidup dalam Kajian Tafsir Tematik - Kartika; Galib, M.; Abubakar, Achmad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The environment in Islam holds profound theological and ecological values, reflected in various verses of the Qur'an. This study aims to analyze the concept of environmental preservation in the Qur'an using a thematic tafsir approach, focusing on verses such as QS. Al-Baqarah (2): 164, QS. Ar-Rum (30): 41, and QS. Al-A’raf (7): 56. These verses highlight the importance of maintaining ecological balance (mizan), the prohibition of excessive behavior (israf), and the warning that ecosystem damage is caused by human actions. Through the thematic tafsir approach, this study finds that the Qur'an provides practical guidance for environmental preservation, such as the protection of flora, fauna, the maintenance of water resources, and the wise management of nature. The concept of khalifah in the Qur'an emphasizes that humans have a significant responsibility to preserve the earth as an amanah (trust) from Allah. This study underscores that environmental preservation is an integral part of Islamic teachings, linking ecological actions to spiritual values. Awareness of the importance of preserving the environment as an amanah from Allah not only impacts the sustainability of ecosystems but also serves as an act of obedience to Him. These findings are highly relevant in addressing modern environmental challenges, such as climate change and pollution, and contribute to the development of environmentally sustainable strategies based on religious values.